2006
DOI: 10.1590/s0103-64402006000100017
|View full text |Cite
|
Sign up to set email alerts
|

Root canal therapy of a maxillary first molar with five root canals: case report

Abstract: This paper reports the case of a maxillary left first molar that presented three root canals in the mesiobuccal root. Root canal therapy and case management are described. Features like wide crown access, adequate illumination and use of exploring files where important for successful completion of the endodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…This information is summarized in Table 1. This case report presents an unusual case of a maxillary first molar with three mesiobuccal canals (two lingual-most canals appeared to join at the middle third) similar to the case reports of David B. Ferguson and Amauri Favieri et al in which two lingual most canals appeared to join at the apical third (13,14). Adanir also reported a similar case with four roots and six canals (8).…”
Section: Discussionsupporting
confidence: 81%
“…This information is summarized in Table 1. This case report presents an unusual case of a maxillary first molar with three mesiobuccal canals (two lingual-most canals appeared to join at the middle third) similar to the case reports of David B. Ferguson and Amauri Favieri et al in which two lingual most canals appeared to join at the apical third (13,14). Adanir also reported a similar case with four roots and six canals (8).…”
Section: Discussionsupporting
confidence: 81%
“…Martinez-Berna and Ruiz-Badanelli (5) reported 3 cases in which the maxillary first molars had presented 6 root canals (3 in MB, 2 in distobuccal [DB], and 1 in palatine root). Favieri et al (1) also showed a similar occurrence in the MB root and reported the difficulty of handling such cases. The occurrence of 2 canals in DB roots has been less frequent and has been reported in 3.6% of maxillary molars (4).…”
mentioning
confidence: 83%
“…The several anatomic variations that might exist in the root canal system have contributed to endodontic treatment failures (1). Maxillary first molars have exhibited a frequent radicular anatomy of 3 roots and 3 or 4 canals (2).…”
mentioning
confidence: 99%
“…Variations in the root canal's anatomy of the root canals play an important role on endodontic therapy success (Chakradhar Raju et al, 2010), mainly in teeth with pulp necrosis (Favieri et al, 2006). It is very important to point out the changes in the root canals morphology in teeth requiring endodontic treatment (Oporto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%